2003
DOI: 10.1039/b210124f
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and trace elements in cloud water and precipitation collected on Mt. Mansfield, Vermont

Abstract: The lack of high quality measurements of Hg and trace elements in cloud and fog water led to the design of a new collector for clean sequential sampling of cloud and fog water. Cloud water was collected during nine non-precipitating cloud events on Mt. Mansfield, VT in the northeastern USA between August 1 and October 31, 1998. Sequential samples were collected during six of these events. Mercury cloud water concentrations ranged from 7.5 to 71.8 ng l(-1), with a mean of 24.8 ng l(-1). Liquid water content exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 50 publications
2
36
2
Order By: Relevance
“…The concentration of Hg(II) used for the model was 0.25 nM. This is equivalent to 50 ng/L, which is within the range of 2.0 to 71.8 ng/L measured in cloud and fog water (Malcolm et al, 2003).…”
Section: Cloud and Fog Water Hg Speciation Modelmentioning
confidence: 67%
“…The concentration of Hg(II) used for the model was 0.25 nM. This is equivalent to 50 ng/L, which is within the range of 2.0 to 71.8 ng/L measured in cloud and fog water (Malcolm et al, 2003).…”
Section: Cloud and Fog Water Hg Speciation Modelmentioning
confidence: 67%
“…Lawson, 1999;Malcolm and Keeler 2002;Malcolm et al, 2003) indicate that mercury is not enriched with respect to its concentration in precipitation as is the case for more soluble compounds. This behavior is expected given the low RGM and particulate-mercury (H p ) Figure 1.…”
Section: Mercury In Precipitationmentioning
confidence: 99%
“…Thus, we performed preliminary experiments (data not published) to evaluate the losses of lichen from and the ingress of macrofauna into bags when using a 1-cm mesh nylon netting; our results demonstrated that the impacts of these two processes are negligible in comparison to the increase in area of exposed surface of lichen. Besides, the use of net bags with a very narrow mesh can allow the condensation of cloud water, which is usually higher in pollutant levels than normal deposition; this could therefore enhance the uptake or concentrations reflected in the lichen measurements (Malcolm et al 2003).…”
Section: Methodsmentioning
confidence: 99%